Research on SDN deployment practice for WAN egress traffic scheduling - Guochun LI; Rui MA; Jichun MA; Bozhong Li; Huiming LIU; Guiyu ZHANG (网络与信息安全学报)
In order to solve the traffic scheduling problem of the WAN exit part,a traffic scheduling optimization method based on SR Policy/EPE was proposed,which simulated and implemented an Internet egress traffic scheduling scheme on the carrier network.The proposed method that can effectively control the flow of business traffic to achieve end-to-end traffic distribution and flexible scheduling of network-wide traffic.Under the premise of ensuring user experience,it effectively improved the utilization of backbone links,optimized the overall network structure,and greatly improved increased network scalability.Apply SR performance measurement function to various performance indicators,and choose the optimal or suboptimal link to solve the WAN exit congestion problem,which proves the feasibility of this solution.